Growth tendencies of the “generation of independence”: the relation between socioeconomic factors and growth indices - Suchomlinov, Andrej; Tutkuvienė, Janina (Acta medica Lituanica, 2013)
Background. The aim of the study was to evaluate the physical status of children born in 1990 in Vilnius City and Region from birth up to the end of puberty, and to investigate the epochal changes and tendencies of their growth. Materials and methods. 1 535 personal health records of children born in 1990 in Vilnius City and Region were analyzed. The main growth indices (height and weight) were recorded from birth up to the age of 18 years. The prevalence of overweight and obesity in children was found using the cut-off points for body mass index recommended by the International Obesity Task Force (Cole et al., 2000). The results of the present study were compared with the results of Lithuanian growth studies, as well as with the growth standards of the World Health Organization (WHO). Results. The prevalence of overweight and obesity in children born in 1990 in Vilnius City and Region was low: 13.60% and 2.40% in the 18-year-old boys and 9.51% and 1.90% in the 18-year-old girls, respectively. The retardation of growth was observed during the first years of independence. The main growth indices have changed in girls more than in boys: both their height (from 166.5 ± 7.0 cm to 167.9 ± 6.2 cm, during the two past decades) and their BMI (from 20.37 ± 2.27 kg/m2 to 21.28 ± 3.33 kg/m2, over the past ten years) increased. Conclusions. Certain retardation in growth of the children born in 1990 was related with the great political, social and economic transition in Lithuania. However, the retardation process was reversible. The main indices of the physical status (height, weight and body mass index) of children did not change much during the two past decades (the acceleration had stabilized). The growth patterns of the “generation of independence” by the end of adolescence showed the tendency towards a higher body weight, though the prevalence of overweight and obesity remained low.